Gold Nanocluster‐Decorated Nickel Nitride as Stable Electrocatalyst for Oxygen Evolution Reaction in Alkaline Media. Issue 22 (28th November 2019) - Lv, Mengyao; Zhou, Ying; Rasaki, Sefiu Abolaji; Shen, Hangjia; Wang, Chuanxi; Song, Weiyu; Thomas, Tiju; Yang, Minghui; Wang, Jun
Abstract: Water electrolysis has received tremendous interest for energy conversion. This is due to its intrinsic eco‐friendliness, and plausibly high efficiencies. However, the efficiency is hampered by sluggish kinetics of the oxygen evolution reaction (OER) at the anode. In this work, co‐precipitation method followed by nitridation is used for fabricating highly efficient and stable Au‐decorated Ni3 N electrocatalyst for OER activity in alkaline solution. The as‐prepared 2 wt % Au at Ni3 N (2 %Au/Ni3 N) nanoflower exhibits remarkable OER. Current density of 10 mA cm −2, Tafel slope of 52 mV/dec, a relatively small overpotential of ∼280 mV, and 94.8 % activity retention for over 10 hour of continuous operation are observed. This remarkable performance is one of the best OER results known so far for noble metal‐supported nanostructured materials using alkaline solution as the electrolyte. From experimental results and calculations thereby, it is found that the Au nanocluster can effectively regulate Ni3 N electronic structure, and reduce the energy barrier associated with OER activity. The synthesis approach given here not only provides a highly efficient electrocatalyst for energy conversion, but also offers a platform for controlling structural characteristics, thereby tuning the catalytic properties of the Au/Ni3 N nanoflowers. Abstract : Gold accents : A co‐precipitation method followed by nitridation is used for fabricating highly efficient and stable Au‐decorated Ni3 N electrocatalyst for the oxygen evolution reaction in alkaline solution. The as‐prepared 2 wt % Au at Ni3 N (2 %Au/Ni3 N) nanoflower exhibits remarkable OER.